KEKERASAN RUMAH TANGGA DALAM PERSFEKTIF HUKUM HINDU - Aditi, I Gusti Ayu (Prodi Hukum Agama Hindu Jurusan Dharma Sastra STAHN Gde Pudja Mataram, 2018)
Theoretically every act against a person, especially a woman, resulting in physical, sexual, psychological and / or abandonment of the physical, sexual, psychological and / or neglect of a household including the threat of unlawful conduct, coercion or deprivation of liberty within the household sphere is an act of domestic violence stairs. Negative labeling by the community that considers women and children to be weak creatures, therefore he is not able to live independently, must be governed, led, well educated. While strong men, lead, organize, and educate women. If violence occurs against ordinary women, but vice versa if the victim of a man's violence becomes extraordinary action. How to